Green synthesis of zerovalent copper nanoparticles for efficient reduction of toxic azo dyes congo red and methyl orange - Ismail Muhammad; Gul Saima; Khan M.I.; Khan Murad Ali; Asiri Abdullah M.; Khan Sher Bahadar (Green Processing and Synthesis, 2019)
In this study, plant-mediated copper nanoparticles (CuNPs) were synthesized. Due to its direct synthesis mechanism and eco-friendly nature, the current method accounts for the green chemistry approach using the fruit extract of Duranta erecta for the first time. The UV-visible spectrum of the CuNPs solution showed a distinct absorption peak at 588 nm. Fourier transform infrared spectroscopy confirmed that the fruit extract is responsible for the reduction as well as the stabilization of CuNPs. X-ray diffraction patterns conform the crystalline nature of CuNPs. Energy-dispersive X-ray spectroscopy was performed for elemental analysis whereas field emission scanning electron microscopy was carried out for surface morphology. Prepared CuNPs were used for the reduction of carcinogenic azo dyes methyl orange (MO) and congo red (CR). CuNPs exhibit outstanding catalytic reduction for MO and CR in the presence of NaBH4 as reducing agents with the pseudo-first-order rate constants of 8.6×10−3 s−1 and 5.07×10−3 s−1 for MO and CR, respectively. Thus, natural plant materials act as cheap and environmentally friendly support for the synthesis of CuNPs and could be used for the purification of water from organic dye effluents.